A note on the movement of a humpback whale from Abrolhos Bank, Brazil to South Georgia - Stevick , Peter T.; De Godoy , Luiza Pacheco; McOsker, Megan; Engel, Marcia H.; Allen, Judith (J. Cetacean Res. Manage., 2023)
Most models of population structure for Southern Hemisphere humpback whales (Megaptera novaeangliae) assume that individuals feeding in the Scotia Sea migrate primarily to breeding and calving areas off Brazil. However data to support this are few and mostly indirect. Abrolhos Bank, Brazil, is the largest breeding and calving ground for humpback whales in the western South Atlantic Ocean. Historically, the waters near South Georgia held the largest concentrations of humpback whales in Antarctic Area II and were among the largest in the Southern Ocean. Photographs of individually distinctive natural markings on humpback whale flukes collected from the Scotia Sea (n=9) were compared with two collections of photographs from Brazilian waters (n=829 and n=735) to identify re-sightings. A humpback whale photographed in August 2000 at Abrolhos Bank was subsequently photographed in December 2004 near Shag Rocks off South Georgia. The migratory distance between these sightings is 3,945km. This finding constitutes the first long-distance individual resighting to be documented from either of these areas.